The impact of abusive use and addiction to social networks on young people - ȘTEFANI, Sebastian Claudiu; MUCEA, Bogdan Nicolae (Presa Universitară Clujeană, 2026)
The phenomenon of excessive digital use cannot be reduced to individual self-control or technological design alone. It is embedded in educational systems, labour markets, family practices, economic incentives, and global crises that increasingly rely on digital mediation. As a result, understanding digital addiction and its related challenges demands a multidisciplinary and critical approach, attentive both to empirical evidence and to the broader cultural meanings of technology in everyday life.